Challenges faced by private developers in developing affordable housing in Kuala Lumpur - Raja Saharudin Raja Muda, 1972- , author 611439 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Sarjana Kejuruteraan (Pengurusan Pembinaan)